Effectiveness of Iloprost in the Treatment of Bone Marrow Edema - Tosun, Haci Bayram; Uludag, Abuzer; Demir, Sukru; Serbest, Sancar; Yasar, Mehmet Mete; Oznam, Kadir (Springernature, 2020)
Background and objective Bone marrow edema (BME) is a rare condition caused by insufficient osseous blood supply and may result in severe pain that has adverse effects on patients' life. To date, various conservative treatments have been recommended for the treatment of BME, including analgesics, immobilization of the affected extremity, and iloprost infusion. The aim of this retrospective study was to investigate the effectiveness of parenteral iloprost therapy in the treatment of BME detected in different skeletal locations. Materials and methods This retrospective study included 23 patients (17 men and six women) with BME who were classified as stage I-III according to the Association Research Circulation Osseous (ARCO) classification. BME was localized to the proximal femur in 13 (56.5%), the distal femur in four (17.4%), tarsal bone in four (17.4%), and tibial plateau in two (8.7%) patients. The mean age of the patients was 46.7 years and all the patients were evaluated with the Visual Analog scale (VAS), Functional Mobility Scale (FMS), and MRI. Results A significant improvement was observed in the post-treatment VAS and FMS scores of all patients compared to their pre-treatment scores. Moreover, the edema regressed completely in 60.9% of the patients at three months of MRI control. No serious side effects were observed during the treatment in any of the patients. However, transient side effects including headache, arrhythmia, and flushing were observed in five patients. Conclusion The present study indicated that iloprost therapy is an effective and safe option in the treatment of BME patients, particularly in the reduction of severe pain that has adverse effects on patients' social life, regardless of ARCO staging. Moreover, this therapy could be particularly useful in reducing pain, improving functional recovery, and achieving complete regression of the edema on MRI in ARCO stage I-II patients.
Keywords: bone marrow edema; iloprost; treatment